Modulation of Humoral and Cell-Mediated Immunity Against Avian Influenza and Newcastle Disease Vaccines by Oral Administration of Salmonella enterica Serovar Typhimurium Expressing Chicken Interleukin-18 - Rahman, Md Masudur (The Korean Association of Immunologists, 2013)
Interleukin-18 (IL-18) has been known to induce interferon-γ (IFN-γ) production and promote Th1 immunity. Although mammalian IL-18 has been characterized in great detail, the properties and application of chicken IL-18 remain largely uninvestigated as of yet. In this study, we evaluated the immunomodulatory properties of Salmonella enterica serovar Typhimurium expressing chicken interleukin-18 (chIL-18) on immune responses induced by avian influenza (AI) and Newcastle disease (ND) vaccines. After oral administration of S. enterica serovar Typhimurium expressing chIL-18, chickens were vaccinated intramuscularly with the recommended dose of either inactivated AI H9N2 vaccine or ND (B1 strain) vaccine. Chickens receiving a primary vaccination were boosted using the same protocol 7 days later. Humoral and cell-mediated immune responses were evaluated in terms of HI antibody titers and proliferation and mRNA expression of IFN-γ and IL-4 of peripheral blood mononuclear cells (PBMC) in response to specific antigen stimulation. According to our results, oral administration of S. enterica serovar Typhimurium expressing chIL-18 induced enhanced humoral and Th1-biased cell-mediated immunity against AI and ND vaccines, compared to that of chickens received S. enterica serovar Typhimurium harboring empty vector. Therefore, we conclude that our proposed vaccination regimen using inactivated AI and ND viruses along with oral administration of S. enterica serovar Typhimurium expressing chIL-18 may provide a novel approach in protecting chicken from currently circulating AI and ND virus strains.